Development of dirhodium(II)-catalyzed generation and enantioselective 1,3-dipolar cycloaddition of carbonyl ylides. - Hodgson, D; Stupple, P; Pierard, F; Labande, A; Johnstone, C (2001)
Catalytic, enantioselective, tandem carbonyl ylide formation/cycloaddition of 2-diazo-3,6-diketoester 2 with the use of dirhodium tetrakiscarboxylate and tetrakisbinaphtholphosphate catalysts to give the cycloadducts 3 in good yields and up to 90% ee is described.